Successful treatment of Clostridioidesdifficile infection with single-donorfaecal microbiota transplantation capsules - Cold, Frederik; Svensson, Camilla Kara; Christensen, Alice Højer; Günther, Stig; Petersen, Andreas Munk; Hansen, Lars Hestebjerg; Helms, Morten (Danish medical journal, 2022)
Treatment of recurrent Clostridioides difficile infection with faecal microbiota transplantation (FMT) is highly effective and is the recommended treatment following a second recurrence. The cure rates of capsule treatment are high (82%-88%). Whether using multi-donor or single-donor FMT capsules affects cure rates remains incompletely understood. A retrospective case series of patients with recurrent, refractory or fulminant C. difficile infection treated for three days with single-donor FMT capsules from October to December 2020 was conducted. The aim of the study was to investigate the clinical efficacy (cure rate) of the treatment and to compare cure rates with previously reported cure rates of treatment with multi-donor FMT capsules produced at the same stool bank. Clinical cure was defined as absence of diarrhoea or diarrhoea with a C. difficile negative stool sample eight weeks after treatment. Clinical cure was observed in 15 of the 18 (83.3%) patients following three days of FMT capsule treatment. Cure rates were comparable (p = 1.0) to previously reported cure rates (88.9%) of multi-donor FMT capsule treatment of recurrent C. difficile infection. Three days of single-donor FMT capsule treatment was effective and safe in the treatment of recurrent, refractory and fulminant C. difficile infection with cure rates comparable to those of multi-donor FMT capsule treatment. This work was supported by the Danish Innovation Fund under Grant 7076-00129B, MICROHEALTH. The funders had no role in the study design, data collection or analysis, the decision to publish, or in the preparation of the manuscript. The FMT capsules from the Aleris-Hamlet FMT Stool Bank were supplied to the Copenhagen University Hospital - Hvidovre Hospital free of charge. not relevant.